2003
DOI: 10.1002/jmv.10485
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of varicella‐zoster virus strains in Germany and differentiation from the Oka vaccine strain

Abstract: With the introduction of varicella vaccination, surveillance of varicella-zoster virus (VZV) strains occurring in cases of chickenpox or zoster should be considered. Differentiating Oka vaccine strain from wild-type VZV can be achieved only using molecular genotyping. In the present study, the VZV genotype was examined in 53 VZV strains isolated from patients with varicella or zoster and in 73 samples from skin eruptions, cerebrospinal fluid, and throat swabs obtained from patients with VZV infections in Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 18 publications
2
40
1
Order By: Relevance
“…The V-Oka vaccine preparations, including the two lots from the same manufacturer, did not contain identical vaccine SNPs. This is consistent with an earlier study showing that the number of R5 repeat regions in V-Oka strains varied from lot to lot (19). Together these findings suggest that the vaccine virus continues to change in culture or alternatively that the manufacturer has used different seed lot preparations for the vaccine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The V-Oka vaccine preparations, including the two lots from the same manufacturer, did not contain identical vaccine SNPs. This is consistent with an earlier study showing that the number of R5 repeat regions in V-Oka strains varied from lot to lot (19). Together these findings suggest that the vaccine virus continues to change in culture or alternatively that the manufacturer has used different seed lot preparations for the vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…: VA 212 A44B-1; GlaxoSmithKline) was used for this study. Two lots were analyzed: V-Oka-GSK-A2, produced in 1999 (19) and used to vaccinate the zoster patient, and V-Oka-GSK-A2, a separate lot produced in 1998. Both vaccine lots were propagated for two passages as described above in HELF.…”
Section: Viral Strains and Their Propagation (I) Oka Varicella Vaccimentioning
confidence: 99%
“…Postlicensure safety surveillance revealed 3,640 cases of vesicular rash (37.4/100,000 doses). The genotyping of VZV was useful to distinguish vaccine strains from wild strains (13,20). In earlier studies, vaccine strains were identified through restriction fragment length polymorphism (RFLP) analysis of the PstI restriction enzyme site in open reading frame (ORF) 38 and the BglI restriction enzyme site in ORF 54 (11 (14).…”
Section: Varicella-zoster Virus (Vzv) Is a Human Herpesvirus That Caumentioning
confidence: 99%
“…Early RFLP analyses revealed both interstrain variations among wild-type isolates and differences between wild-and vaccine-type viruses. The most commonly used RFLP markers of VZV included the polymorphism of open reading frames (ORFs) 38 (PstI), 54 (BglI), and 62 (SmaI) (19,23,45). These markers allowed the majority of wild-type strains in North America and Europe to be typed as PstI ϩ BglI Ϫ , whereas African and Asian strains were BglI ϩ and Japanese Oka-like wild-type strains were PstI ϩ /PstI Ϫ BglI ϩ SmaI Ϫ ; the Oka vaccine strains were PstI Ϫ BglI ϩ SmaI ϩ (20,40,47).…”
mentioning
confidence: 99%